MANAGING POVERTY AND INSECURITY IN NIGERIA SCHOOLS (Scientific Journal of Educational Management, Research and law, 2025)
This paper review centersit’s discussion on “Managing Poverty and Insecurity in Nigeria Schools”, secondary data were used to support the point raised in this work. The data were sourced from print materials and online publications by recognized institutions and individual authors. The paper identified unemployment, poverty, illiteracy, marginalization, political factors, international influence and communalcrisis as the bane of insecurity in Nigeria. The paper also identified loss of man power in educational institutions, poor quality of Education, destructions of infrastructural facilities, brain-drain, closure of Educational Institutions, discouragement of educational pursuit by children, internal displacement of learners, reduction of private investment in Education and inadequate funding of Education as the impact of insecurity on school administration in Nigeria. In order to address the challenges of insecurity on schooladministration in Nigeria, this paper recommends among other things: That government should ensure that, the political will to fight all forms of insecurity in the country through the application of best strategies are honestly and sincerely put in place.